2010
DOI: 10.1094/phyto-100-9-0913
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Systemic Resistance in Plants by Biochar, a Soil-Applied Carbon Sequestering Agent

Abstract: Biochar is the solid coproduct of biomass pyrolysis, a technique used for carbon-negative production of second-generation biofuels. The biochar can be applied as a soil amendment, where it permanently sequesters carbon from the atmosphere as well as improves soil tilth, nutrient retention, and crop productivity. In addition to its other benefits in soil, we found that soil-applied biochar induces systemic resistance to the foliar fungal pathogens Botrytis cinerea (gray mold) and Leveillula taurica (powdery mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(171 citation statements)
references
References 60 publications
6
139
1
2
Order By: Relevance
“…Biochar application not only improves crop productivity by modifying the soil structure, pH, cation exchange capacity, porosity, water holding capacity and by increasing the nutrient retention and availability but also stimulates the plant defence system through biochar-borne elicitor chemicals (Sohi et al 2010;Elad et al 2010). However, in some studies different biochar types (depending on feedstock and pyrolysis temperature) have been reported to negatively affect crop yield, soil properties and beneficial soil microbiota (Mukherjee and Lal 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar application not only improves crop productivity by modifying the soil structure, pH, cation exchange capacity, porosity, water holding capacity and by increasing the nutrient retention and availability but also stimulates the plant defence system through biochar-borne elicitor chemicals (Sohi et al 2010;Elad et al 2010). However, in some studies different biochar types (depending on feedstock and pyrolysis temperature) have been reported to negatively affect crop yield, soil properties and beneficial soil microbiota (Mukherjee and Lal 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Jaiswal et al (2014Jaiswal et al ( , 2015 demonstrated the dependency of the disease suppressing ability of different biochars on the feedstock and production parameters. Biochar-induced systemic resistance was documented against gray mold (Botrytis cinerea) and powdery mildew (Oidiopsis sicula) on pepper and tomato (Elad et al 2010). Recently, Jaiswal et al (2015) reported that the biochar application suppresses damping off (Rhizoctonia solani) on common bean (Phaseolus vulgaris L.) seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Elad et al (2010) and Harel et al (2012) reported on positive effects of biochar on decreasing foliar fungal infections in tomatoes, pepper and strawberry. Improved plant responses to diseases can be yet another benefit of applying biochar to soil (Elad et al, 2011).…”
Section: Determining Factors and Potential Effects Of Biochar On Soilmentioning
confidence: 99%
“…This can be seen in the formulations G, wherein the formulation without the addition of nutrients may result in nutrient limitation. According Kresnawaty et al [11] on biocharcoal carbon available in the form of crystals and aromatic making it difficult to use by the fungus, while the germination of the fungus requires C and N. Elad et al [18] reported that biocharcoal in low doses (1%-5%) contain residual tars compound which have been found to aid seeds germination and trigger the growth of microorganisms and have biocidal properties.…”
Section: Resultsmentioning
confidence: 99%